2013
DOI: 10.1002/zaac.201300379
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Decomposition of Metastable α′′‐Fe16N2 from in situ Powder Neutron Diffraction and Thermal Analysis

Abstract: Abstract. In order to gain more information on the formation and decomposition behavior of metastable αЈЈ-Fe 16 N 2 from different starting materials in situ neutron diffraction and thermal analysis in different gas atmospheres and heating rates were carried out. Under inert conditions a direct conversion of αЈЈ-Fe 16 N 2 in α-Fe and N 2 was observed using higher heating rates, while with lower heating rates the decomposition occurs via the formation of γЈ-Fe 4 N y . The changes in c/a ratio of the αЈЈ-phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 87 publications
2
35
0
Order By: Relevance
“…A similar behavior was previously observed in a lower temperature region for the thermal decomposition of αЈЈ-Fe 16 N 2 . [15] Additionally, a second nitrogen transfer mechanism is observed: Especially for ζ-Fe 2 N and ε-Fe 3 N 1+x with decreasing amount of the respective nitride phase ( Figure 2) the nitrogen content increases (Figure 3), which means most of the nitrogen is first enriched in the respective phase, before a gradual conversion into the next stable phase proceeds. According to the smaller heating rate applied in the in situ neutron diffraction experiment, all phase transitions, especially those related to a release of N 2 , are observed at lower temperatures than in previous TG experiments.…”
Section: Investigations On the Decomposition Behavior Of ζ-Fe 2 Nmentioning
confidence: 92%
See 2 more Smart Citations
“…A similar behavior was previously observed in a lower temperature region for the thermal decomposition of αЈЈ-Fe 16 N 2 . [15] Additionally, a second nitrogen transfer mechanism is observed: Especially for ζ-Fe 2 N and ε-Fe 3 N 1+x with decreasing amount of the respective nitride phase ( Figure 2) the nitrogen content increases (Figure 3), which means most of the nitrogen is first enriched in the respective phase, before a gradual conversion into the next stable phase proceeds. According to the smaller heating rate applied in the in situ neutron diffraction experiment, all phase transitions, especially those related to a release of N 2 , are observed at lower temperatures than in previous TG experiments.…”
Section: Investigations On the Decomposition Behavior Of ζ-Fe 2 Nmentioning
confidence: 92%
“…Additionally, three stable iron nitride phases are present: γЈ-Fe 4 N y with only a small homogeneity range, ε-Fe 3 N 1+x with a broad phase width, and ζ-Fe 2 N with an again narrow range of compositions. [20] Furthermore, four metastable phases are reported in literature: bct αЈ-Fe 8 N, αЈЈ-Fe 16 N 2 as an order-variant thereof, [15,21] FeN in rock salt [22] and in sphalerite structure types. [23] Nitrogen austenite (γ-FeN z ) is only stable above 592°C.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…By a combination of thermal analysis and in situ neutron powder diffraction it was shown that all reactions upon formation and decomposition of αЈЈ-Fe 16 N 2 are kinetically controlled and the yield of synthesis could thus be increased to above 90 % (Figure 6). [106] In situ NPD of the ammonolysis of chromium(III) compounds like chromium(III) sulfide Cr 2 S 3 or anhydrous chromium(III) chloride CrCl 3 to form thermodynamically stable chromium(III) nitride (γ-CrN) revealed a surprising reduction-oxidation sequence. In case of the ammonolysis of Cr 2 S 3 the reduction to chromium(II,III) sulfide Cr 3 S 4 was observed followed by re-oxidation to Cr III in the formation of thermodynamically stable γ-CrN.…”
Section: /Kap1mentioning
confidence: 99%
“…Chromium powder was reacted in a silica glass tube [42,43] in the high temperature resistive furnace (HTF) of the SPODI diffractometer (FRM-II, Garching) with flowing ammonia (60 cm 3 ·min -1 ). During the reaction powder neutron diffraction was recorded with an effective time resolution of 90 min and an angular resolution of Δ(2Θ) = 0.1° (Figure 1).…”
Section: Synthesis Of Chromium Nitride From Chromium and Ammoniamentioning
confidence: 99%